2014
DOI: 10.1186/cc13745
|View full text |Cite
|
Sign up to set email alerts
|

Development of a simple score to predict outcome for unresponsive wakefulness syndrome

Abstract: IntroductionAccurate assessment of prognosis for patients with unresponsive wakefulness syndrome (UWS; formerly vegetative state) may help clinicians and families guide the type and intensity of therapy; however, there is no suitable and accurate means to predict the outcome so far. We aimed to develop a simple bedside scoring system to predict the likelihood of awareness recovery in patients with UWS.MethodsWe prospectively enrolled 56 patients (age range 10 to 73 years) with UWS 3 to 12 weeks post-onset. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 46 publications
3
27
1
Order By: Relevance
“…Compared with patients with good prognosis, patients with poor prognosis had less frequent reactive EEG patterns as well as sleep architecture ( p < 0.004). Pediatric CPC Kang et al (2014) [ 61 ] Mixed 56 Performance of the variable reactive EEG for recovery of awareness: OR = 21.648 (2.212 to 211.870). 66.7 (44.7–83.6) 75.0 (56.2–87.9) 66.7 (44.7–83.6) 75.0 (56.2–87.9) GOS at 1 year follow-up Visual only Bagnato et al (2017) [ 33 ] Mixed 28 5 of the 16 patients with consciousness improvement showed EEG-R on baseline EEG (at admission), which was absent in all patients without improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with patients with good prognosis, patients with poor prognosis had less frequent reactive EEG patterns as well as sleep architecture ( p < 0.004). Pediatric CPC Kang et al (2014) [ 61 ] Mixed 56 Performance of the variable reactive EEG for recovery of awareness: OR = 21.648 (2.212 to 211.870). 66.7 (44.7–83.6) 75.0 (56.2–87.9) 66.7 (44.7–83.6) 75.0 (56.2–87.9) GOS at 1 year follow-up Visual only Bagnato et al (2017) [ 33 ] Mixed 28 5 of the 16 patients with consciousness improvement showed EEG-R on baseline EEG (at admission), which was absent in all patients without improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Although EEG reactivity was measured to very different stimuli [e.g., to passive ( 23 ) or forced eyes opening ( 19 , 20 ), to pain ( 34 , 41 ), to warm water ( 39 ), and no description was given by Sarà et al ( 48 )] and the definition of reactivity substantially varied, the results are very homogenous across the reports. Moreover, this was the only group of predictor variables whose predictive value was significant for both improvement criteria (transition from UWS to MCS and the recovery of consciousness).…”
Section: Discussionmentioning
confidence: 99%
“…The subjectivity can, of course, be avoided if we decide for purely automatic methods (Kang et al ., ; Malinowska et al ., ). This strategy, however, is related to the risk to obtain quantitative data whose functional meaning may be difficult to interpret.…”
Section: Introductionmentioning
confidence: 99%